A quick guide to pipeline engineering - Alkazraji, D. (Cambridge, England : Woodhead Publishing, 2008)
Pipeline engineering requires an understanding of a wide range of topics. Operators must take into account numerous pipeline codes and standards, calculation approaches, and reference materials in order to make accurate and informed decisions. A Quick Guide to Pipeline Engineering provides concise, easy-to-use, and accessible information on onshore and offshore pipeline engineering. Topics covered include: design; construction; testing; operation and maintenance; and decommissioning. Basic principles are discussed and clear guidance on regulations is provided, in a way that will prove useful to both engineers and students.
Includes bibliographic references and index
Keywords: Pipelines -- Design and construction